Fecal microbiota transplantation augments 5-fluorouracil efficacy in pancreatic cancer via gut microbiota modulation - Li, Rui; Hu, Yaoyuan; Liu, Yixian; Tan, Xiaodong (Frontiers in Microbiology, 2025)
BackgroundPancreatic cancer is a highly aggressive malignancy with limited therapeutic options due to rapid tumor progression and poor prognosis. Fecal Microbiota Transplantation (FMT) has emerged as a promising approach to modulate gut microbiota, potentially enhancing the efficacy of conventional treatments.ObjectivesThis study evaluates the combined effects of FMT and 5-fluorouracil (5FU) on gut microbiota composition, pancreatic tumor growth, and systemic immune responses in a murine model.MethodsOne hundred female C57BL/6 mice aged 6–8 weeks were randomly divided into five groups (n = 20 each): Sham, Model, FMT, 5FU, and FMT + 5FU. Pancreatic tumors were induced via orthotopic implantation of Pan02 cells. FMT was administered orally (0.2 g fecal material) three times per week, starting 2 weeks before tumor implantation. 5FU was administered intraperitoneally at 25 mg/kg body weight twice weekly, beginning one-week post-tumor implantation. Gut microbiota was analyzed via 16S rRNA gene sequencing of fecal samples after 10-week cell implantation. Tumor volumes were measured, and serum cytokine levels were assessed. Short-chain fatty acids (SCFAs) in blood and feces using gas chromatography–mass spectrometry (GC–MS).ResultsThe FMT + 5FU group exhibited the smallest average tumor volume, significantly smaller than the Model (p < 0.0001) and 5FU groups (p = 0.005). FMT alone reduced tumor volume compared to the Model group (p < 0.0001). Gut microbiota analysis revealed increased α diversity in the FMT group compared to the Model group (p < 0.0001). The FMT + 5FU group showed a significant reduction in cytokine levels, including TNF-α (p = 0.0001) and IL-6 (p = 0.012) and increased IL-10 level (p < 0.001), compared to the Model group. Plasma and fecal SCFA concentrations were significantly higher in both FMT and FMT + 5FU groups relative to the Model group (p < 0.001). Additionally, the FMT + 5FU group had the highest survival rate (50%) after 10-week cell implantation, compared to the Model group (15%).ConclusionFMT significantly enhances the efficacy of 5FU in reducing pancreatic tumor growth through gut microbiota modulation.